Plan estratégico para la comercializadora "INJORI CIA LTDA" de la ciudad de Loja. - Cobos Galván, Cristina Lizbeth (2016)
The marketing "CIA LTDA INJORI" business reason for this study had to change and extreme new strategies to keep growing competition in the market, but all these efforts have not been enough having to be a technical deeper market environment and the internal of the company, with this background has been the need for a strategic plan to identify and implement future strategies for the best chance of success, through a permanent position of this company on the market. Where the point of analysis currently focuses on the importance of proper strategic planning today because of competition and survival in the market focus on: Customer satisfactions, greater percentage of them hoard and provide quality services. With regard to methods and techniques used to perform this research, we applied literature survey, document review, direct observations of the operation and services provided by the marketer "INJORI CIA LTDA" plus an interview was made its president; Likewise was applied to two types of surveys, the first at 5 workers at the company, and the second survey of a representative sample of 145 commercial establishments wholesale consumer products in the city of Loja. In order to obtain information necessary for the development of this research. Also conducted a SWOT analysis, which gave me to know and identify: strengths, weaknesses, opportunities and threats of this company. With the testing of these elements, built strategies to improve internal and external aspects, leveraging their strengths, to seize opportunities, reduce weaknesses and neutralize threats, identification of these internal and external factors allowed me to make high-impact matrix and weighting to structure a new SWOT matrix. Finally there was a proposal based on a strategic plan to improve the operation and services of the company, the same as is the implementation of 4 strategic objectives: The first refers to the administrative structure designed to improve the internal activities of the company, the cost of dissemination amounts to $ 80.00; The second strategic objective is planned to carry out a plan for promotion and advertising through various local media, in order to meet the commercial services offered by the marketer to wholesale customers in the city of Loja at a cost of $ 1020.00 only referring to what will be advertising as it is not assigned a fixed cost promotions as it is indeterminate the number of discounts that are made to customers and wedges commercial to be developed. The third strategic objective is about developing a training plan to educate workers and staff the cost of dissemination amounts to $ 2615.50, in order to improve trade relations and service to wholesale customers in the city the cost of this target will be covered with core business earnings, raises gain entry to new markets offering consumer products at affordable prices and providing credit facilities at a cost of $ 1,288.00, the total cost of the proposed strategic plan amounts to a total of $ 5,003.50. Finally, we present the conclusions and recommendations have been determined, after study by the strategic planning process, the same to be brought to the attention of managers of the marketing "CIA LTDA INJORI" for later execution.